A Study on Management of Health Care Infrastructure Development in Rural India: Critical analysis of current status and future challenges - Nenavath Sreenu (ACHSM, 2018)
The study has focused on the role of rural health infrastructure development in India. Currently the health infrastructure development of India is poor and it needs fundamental reforms to deal with new emerging challenges. The role of private providers is increasing but simultaneously healthcare facilities are becoming costly. The study surveys the present position of rural health care infrastructure growth, the development of infrastructure, health care facilities, position of human resource, and quality of service delivery. The paper suggests future challenges of Indian healthcare infrastructure development in rural area, as the burden of disease, financial deficiency in a large section of the population, vaccination policy and poor access to health care. Longevity, literacy and per capita income are further considerations.